Changes in treatment of community-onset Clostridioides difficile infection after release of updated guidelines, Atlanta, Georgia, 2018. (August 2021) - Adelman, Max W.; Goodenough, Dana; Sefton, Samantha; Mackey, Carolyn; Thomas, Stepy; Fridkin, Scott K.; Woodworth, Michael H.
Abstract: Updated Clostridioides difficile infection (CDI) guidelines published in 2018 recommend vancomycin as first-line treatment. Of 833 community-onset CDI cases in metropolitan Atlanta, Georgia in 2018, over half did not receive first-line treatment, although guideline adherence increased over the year. Second-line treatment was more common in patients treated in ambulatory settings. Graphical abstract: Image 1 Highlights: 2018 Clostridioides difficile guidelines recommend treatment with vancomycin. Use of vancomycin increased throughout the year after guideline publication. Patients treated in an ambulatory setting were less likely to receive vancomycin. These findings can help target education to improve guideline-adherent prescribing.